Poczucie własnej skuteczności a zachowania zdrowotne = Self-efficacy and health behawior - Baumgart, Mariusz; Szpinda, Michał; Radzimińska, Agnieszka; Goch, Aleksander; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Baumgart Mariusz, Szpinda Michał, Radzimińska Agnieszka, Goch Aleksander, Zukow Walery. Poczucie własnej skuteczności a zachowania zdrowotne = Self-efficacy and health behawior. Journal of Education, Health and Sport. 2015;5(8):226-235. ISSN 2391-8306. DOI 10.5281/zenodo.28074 http://dx.doi.org/10.5281/zenodo.28074 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A226-235 https://pbn.nauka.gov.pl/works/607775 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 12.08.2015. Poczucie własnej skuteczności a zachowania zdrowotne Self-efficacy and health behavior Mariusz Baumgart1, Michał Szpinda1, Agnieszka Radzimińska2, Aleksander Goch2, Walery Zukow3 1. Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Anatomii Prawidłowej, Bydgoszcz, Polska 2. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 3. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska, Wydział Kultury Fizycznej, Zdrowia i Turystyki Autor do korespondencji dr. n.med. Mariusz Baumgart e-mail: baumgartmar@gmail.com Streszczenie Wstęp Czynnikiem mającym ogromny wpływ na nasze zdrowie jest styl życia. Elementami składowymi stylu życia są różne kategorie zachowań ludzkich, w tym także zachowania zdrowotne. Czynnikiem determinującym wiele aspektów ludzkiego zachowania jest poczucie własnej skuteczności. Materiał i Metody Badaniami objęto 150 osób (84 kobiety i 66 mężczyzn) w wieku 20 – 37 lat (średnia wieku 27,95, SD=5,02). W badaniach wykorzystano Inwentarz Zachowań Zdrowotnych (IZZ) i Skalę Uogólnionej Własnej Skuteczności (GSES). Wyniki Wykazano istotną statystycznie (p<0,05) dodatnią korelację między wynikami wszystkich kategorii kwestionariusza IZZ i skali GSES. Słowa kluczowe: zachowania zdrowotne, poczucie własnej skuteczności. Summary Introduction The factor that had a huge impact on our health is a lifestyle. The components of lifestyle are different categories of human behavior, including health behaviors. The factor which determines many aspects of human behavior is self-efficacy. Material and Methods The study involved 150 people (84 women and 66 men) aged 20 - 37 years (mean age 27.95, SD = 5.02). The study used the Health Behaviour Inventory and Generalized Self Efficacy Scale. Results It has been shown statistically significant (p <0.05) positive correlation between the results of all categories IZZ questionnaire and GSES. Key words: health behavior, self-efficacy.